Inheritance [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Lost bride trilogy., 2023)
"Inheritance is the first in The Lost Bride Trilogy by #1 New York Times bestselling author Nora Roberts--a tale of tragedies, loves found and lost, and a family haunted for generations. 1806: Astrid Poole sits in her bridal clothes, overwhelmed with happiness. But before her marriage can be consummated, she is murdered, and the circle of gold torn from her finger. Her last words are a promise to Collin never to leave him... Graphic designer Sonya MacTavish is stunned to learn that her late father had a twin he never knew about--and that her newly discovered uncle, Collin Poole, has left her almost everything he owned, including a majestic Victorian house on the Maine coast, which the will stipulates she must live in it for at least three years. Her engagement recently broken, she sets off to find out why the boys were separated at birth--and why it was all kept secret until a genealogy website brought it to light. Trey, the young lawyer who greets her at the sprawling clifftop manor, notes Sonya's unease--and acknowledges that yes, the place is haunted...but just a little. Sure enough, Sonya finds objects moved and music playing out of nowhere. She sees a painting by her father inexplicably hanging in her deceased uncle's office, and a portrait of a woman named Astrid, whom the lawyer refers to as "the first lost bride." It's becoming clear that Sonya has inherited far more than a house. She has inherited a centuries-old curse, and a puzzle to be solved if there is any hope of breaking it..."--